2005
DOI: 10.1021/np049710z
|View full text |Cite
|
Sign up to set email alerts
|

Rhizochalin A, a Novel Two-Headed Sphingolipid from the Sponge Rhizochalina incrustata

Abstract: Rhizochalin A (4), the fourth representative of two-headed glycosphingolipids, was isolated as its peracetate from the sponge Rhizochalina incrustata. Its structure has been established as the 2-ethyl carbamoate of rhizochalin on the basis of spectroscopic data and chemical transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…7,11) From these results, we concluded that the minimum Rhz structure necessary for apoptosis induction in HL-60 cells is one possessing a twoheaded sphingosine. Moreover, our study suggests that the aglycon derivatives of Rhz or its analog AglRhzA induce apoptosis more effectively than intact Rhz or its peracetylated derivatives, which makes the former better analogs of two-headed sphingolipids than the intact toxin as anti-tumor agents.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…7,11) From these results, we concluded that the minimum Rhz structure necessary for apoptosis induction in HL-60 cells is one possessing a twoheaded sphingosine. Moreover, our study suggests that the aglycon derivatives of Rhz or its analog AglRhzA induce apoptosis more effectively than intact Rhz or its peracetylated derivatives, which makes the former better analogs of two-headed sphingolipids than the intact toxin as anti-tumor agents.…”
Section: Discussionmentioning
confidence: 87%
“…The D-galactose is the most common sugar encountered among the Rhzs from the sponge R. insrustata. 7) Hydrolysis of Rhz yields the aglycon derivatives. Results of the present study show that aglycon derivatives are more potent than Rhz in inducing apoptosis of HL-60 cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations